Analysis Of The Components And Content Of The Apollo Dictionary As A Learning Resource For Arabic - Anjani, Hafsah; Tatang, Tatang; Shofa Musthofa Khalid (Universitas Cokroaminoto Palopo, 2025)
Dictionaries are one of the primary learning resources, particularly in Arabic language learning. The Apollo dictionary has been a learning resource for over two years at an Islamic boarding school, but no analysis has been conducted on its components. This study aims to examine the dictionary's content and components, specifically the Apollo dictionary as a learning resource for students, and provide recommendations for improvement and usage. This research employs descriptive analysis with document analysis data collection techniques. The results show that this dictionary can be used as a learning resource due to its user-friendly conciseness. However, additional components, such as source references, are necessary for dictionary components. This is crucial for student dictionaries. Nevertheless, the dictionary should also be tailored to students' needs, considering both conciseness and completeness.